Gastric Dysmotility in Critically Ill Children: Pathophysiology, Diagnosis, and Management*. Issue 9 (November 2015) - Martinez, Enid E.; Douglas, Katherine; Nurko, Samuel; Mehta, Nilesh M.
Abstract : Objective: We aimed to review gastric dysmotility in critically ill children: 1) its pathophysiology, with a focus on critical care diseases and therapies that affect gastric motility, 2) diagnostic methodologies, and 3) current and future potential therapies. Data Sources: Eligible studies were identified from PubMed and MEDLINE. Study Selection: Literature search included the following key terms: "gastric emptying, " "gastric motility/dysmotility, " "gastrointestinal motility/dysmotility, " "nutrition intolerance, " and "gastric residual volume." Data Extraction: Studies since 1995 were extracted and reviewed for inclusion by the authors related to the physiology, pathophysiology, diagnostic methodologies, and available therapies for gastric emptying. Data Synthesis: Delayed gastric emptying, a common presentation of gastric dysmotility, is present in up to 50% of critically ill children. It is associated with the potential for aspiration, ventilator-associated pneumonia, and inadequate delivery of enteral nutrition and may affect the efficacy of enteral medications, all of which may be result in poor patient outcomes. Gastric motility is affected by critical illness and its associated therapies. Currently available diagnostic tools to identify gastric emptying at the bedside have not been systematically studied and applied in this cohort. Gastric residual volume measurement, used as an indirect marker of delayed gastric emptying in PICUs around the world, may be inaccurate. Conclusions: Gastric dysmotility is common in critically ill children and impacts patient safety and outcomes. However, it is poorly understood, inadequately defined, and current therapies are limited and based on scant evidence. Understanding gastric motility and developing accurate bedside measures and novel therapies for gastric emptying are highly desirable and need to be further investigated.